MDCK and Vero cells for influenza virus vaccine production: a one-to-one comparison up to lab-scale bioreactor cultivation - Genzel, Yvonne (Appl Microbiol Biotechnol, 2010)
Over the last decade, adherent MDCK (Madin Darby canine kidney) and Vero cells have attracted considerable attention for production of cell culture-derived influenza vaccines. While numerous publications deal with the design and the optimization of corresponding upstream processes, one-to-one comparisons of these cell lines under comparable cultivation conditions have largely been neglected. Therefore, a direct comparison of influenza virus production with adherent MDCK and Vero cells in T-flasks, roller bottles, and lab-scale bioreactors was performed in this study. First, virus seeds had to be adapted to Vero cells by multiple passages. Glycan analysis of the hemagglutinin (HA) protein showed that for influenza A/PR/8/34 H1N1, three passages were sufficient to achieve a stable new N-glycan fingerprint, higher yields, and a faster increase to maximum HA titers. Compared to MDCK cells, virus production in serum-free medium with Vero cells was highly sensitive to trypsin concentration. Virus stability at 37 °C for different virus strains showed differences depending on medium, virus strain, and cell line. After careful adjustment of corresponding parameters, comparable productivity was obtained with both host cell lines in small-scale cultivation systems. However, using these cultivation conditions in lab-scale bioreactors (stirred tank, wave bioreactor) resulted in lower productivities for Vero cells.